Analisis Ekonomi Awal Proses Produksi Biobutanol dari Tandan Kosong Sawit dengan Proses Hidrolisis dan Fermentasi Secara Terpisah - Reno Susanto; Tjokorde Walmiki Samadhi; Winny Wulandari; Said Zul Amraini (Fakultas Teknik - Universitas Jenderal Achmad Yani, 2022)
The limitation of petroleum reserves and environmental issues have led countries worldwide to shift towards producing and utilizing biofuels as an alternative solution to replace fossil fuels. One of the biofuels that can be used is biobutanol, which can be produced from residual waste containing lignocellulose. An empty fruit bunch (EFB) from oil palm is a residual waste used as raw material for biobutanol production. The method that can be used in biobutanol production is the Separated Hydrolysis and Fermentation (SHF) process, which allows the cellulose hydrolysis process to be pre-treated with acid at lower temperature but for longer time or at higher temperature for shorter time. The product from Clostridium acetobutylicum using hydrolysate from cellulose hydrolysis is higher than that from acid hydrolysis. The cellulase enzyme hydrolysis process can be separated from the fermentation process according to their optimum conditions. From the initial economic analysis calculation with production basis of 10,000 tons per year, total gross profit margin of IDR 39,459/kg was obtained, indicating that biobutanol production from EFB biomass is economically feasible and profitable. Further study is needed to conduct a techno-economic analysis of the biobutanol production process using EFB as raw material.